De novo steroid biosynthesis in human prostate cell lines and biopsies. Issue 6 (4th February 2016) - Sakai, Monica; Martinez‐Arguelles, Daniel B.; Aprikian, Armen G.; Magliocco, Anthony M.; Papadopoulos, Vassilios
Abstract : BACKGROUND: Intratumoral androgen formation may be a factor in the development of prostate cancer (PCa), particularly castration‐resistant prostate cancer (CRPC). To evaluate the ability of the human prostate to synthesize de novo steroids, we examined the expression of key enzymes and proteins involved in steroid biosynthesis and metabolism. METHODS: Using TissueScan™ Cancer qPCR Arrays and quantitative RT‐PCR, we performed comparative gene expression analyses between various prostate cell lines and biopsies, including normal, hyperplastic, cancerous, and androgen‐deprived prostate cells lines, as well as normal, benign prostate hyperplasia (BPH), PCa, and CRPC human specimens. These studies were complemented with steroid biosynthesis studies in normal and BPH cells. RESULTS: Normal human prostate WPMY‐1 and WPE1‐NA22, benign prostate hyperplasia BPH‐1, and cancer PC‐3, LNCaP, and VCaP cell lines, as well as normal, BPH, PCa, and CRPC specimens, were used. Although all cell lines express mRNA encoding for hydroxymethylglutaryl‐CoA reductase ( HMGCR ), the mitochondrial translocator protein TSPO and cholesterol side chain cleavage enzyme CYP11A1 were only observed in WPMY‐1, BPH‐1, and LNCaP cells. HSD3B1, HSD3B2, and CYP17A1 are involved in androgen formation and were not found in most cell lines. WPE1‐NA22 and BPH‐1 cells were unable to synthesize de novo steroids from mevalonate. Moreover, androgen‐deprived cells did not have alterations in the expression of enzymes that could lead to de novo steroid formation. All prostate specimens expressed TSPO and CYP11A1 . HSD3B1/2, CYP17A1, HSD17B5, and CYP19A1 mRNA expression was distinct to the profile observed in cells lines. The majority of BPH (90.9%) and PCa (83.1%) specimens contained CYP17A1, compared to control (normal) specimens (46.7%). BPH (82%), PCa (59%), normal (40%), and CRPC (34%) specimens expressed the four key enzymes that metabolize cholesterol to androgens. CONCLUSION: These studies question the use of prostate cell lines to study steroid biosynthesis and demonstrate that human prostate samples contain transcripts encoding for key steroidogenic enzymes and proteins indicating that they have the potential to synthesize de novo steroids. We propose CYP17A1 as a candidate enzyme that can be used for patient stratification and treatment in BPH and PCa. Prostate 76:575–587, 2016 . © 2016 Wiley Periodicals, Inc.